PLAYFUL TRAINING FOR TEACHERS OF EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2013)
This article is part of a project socialization training of kindergarten teachers in the context of work on Municipal Drive Early Childhood Education (UEI) Pratinha integrated the Municipal School of Belém / Pa, developed in 2012. It is based on the theoretical framework of Debortoli (2009), Kishimoto (2002), Fortune (2012) among others. Aimed to promote awareness about childhood games; provide a playful dimension in teacher training for early childhood education, pointing out the contributions of play to the comprehensive development of babies, toddlers and preschoolers; include the games as learning situations in context of early childhood education. The methodological approach adopted was subsidized by the qualitative approach, understanding that best responds to the theme linked to human phenomena, social or educational, which often do not allow to be measurable or quantifiable. In qualitative research the subject, in this case, teacher and trainer, were involved in a production situation of knowledge about the reality in which they are immersed, giving the meanings, interpretations, meanings and or (re) significations. Relevant aspects of this work lie in the quality of early childhood education teaching practice mediated processes jokes and playful, as when planning space and time to play allows up welcoming environments, challenging, interactive and inventive, valuing knowledge, languages, experiences and knowledge of the child, therefore, is proposed to play and brincantes pedagogical practice that is likely to meet the needs and interests of children legitimizing an education articulated playful dimensions expressive-motor, affective, cognitive, linguistic, ethical, aesthetic and socio-cultural child in favor of their integral formation.
Keywords: Jokes; Early Childhood Education; Training playful